ANALISIS KEPUASAN KERJA BERDASARKAN MOTIVASI KERJA DAN KOMITMEN ORGANISASI DAMPAKNYA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi Kasus pada Pegawai Dinas Pendidikan Dayah - Bireuen) - Martunis Usman; Ibrahim Ibrahim; Nadia Salsabillah (IndOmera, 2025)
This study observes OCB from the impact of job satisfaction by considering motivational factors and organizational commitment. The study was conducted on employees of the Dayah Education Office in Bireuen district, with a quantitative associative research type. Problem analysis uses path analysis model statistics. Data collection through questionnaires on a sample of 40 employees as respondents. The results show that there are: (1) Direct and indirect impacts of work motivation on job satisfaction, through the organizational commitment variable, which is 23.15%. Likewise, the impact of organizational commitment on job satisfaction, through the work motivation variable, which is 20.89%. (2) Simultaneously, work motivation and organizational commitment contribute 53.5% to job satisfaction. (3) The direct and indirect effects of work motivation on OCB, with the existence of organizational commitment, amounting to 62.47%. And the direct/indirect effect of organizational commitment is 36.17%. (4) Simultaneously, work motivation and organizational commitment contribute 55.9% to OCB. (5) The total influence of work motivation and organizational commitment on organizational citizenship behavior (OCB), through the variable of employee job satisfaction, is 22.98%.